2012
DOI: 10.1007/s10608-012-9483-2
|View full text |Cite
|
Sign up to set email alerts
|

Keep Your Eye on the Target: Safety Behavior Reduces Targeted Threat Beliefs Following a Behavioral Experiment

Abstract: This study examined the effect of safety behavior on belief change during a behavioral experiment. Highly spider fearful participants (N = 126) evaluated a targeted negative belief about spiders during a brief behavioral experiment with a live tarantula. Participants were randomly assigned either to use or not use safety gear during the session. Results demonstrated that after the behavioral experiment, targeted negative beliefs were significantly lower in the safety gear condition than in the control conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…A few studies that used protective gear (e.g., gloves, goggles, corresponding to PSB) have shown benign or beneficial outcomes in the confines of snake (Milosevic & Radomsky, 2008) and spider phobias (Milosevic & Radomsky, 2013). Why would PSB have varying impact across studies?…”
Section: Discussionmentioning
confidence: 99%
“…A few studies that used protective gear (e.g., gloves, goggles, corresponding to PSB) have shown benign or beneficial outcomes in the confines of snake (Milosevic & Radomsky, 2008) and spider phobias (Milosevic & Radomsky, 2013). Why would PSB have varying impact across studies?…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more recent studies have found comparable outcomes in exposure therapy with and without safety behavior (Deacon, Sy, Lickel, & Nelson, 2010;Hood, Antony, Koerner, & Monson, 2010;Milosevic & Radomsky, 2008, 2013bRachman, Shafran, Radomsky, & Zysk, 2011;van den Hout, Engelhard, Toffolo, & van Uijen, 2011). Lack of understanding regarding how to appropriately categorize safety behaviors as adaptive versus maladaptive coping strategies may explain these mixed findings (McKay, 2010;Thwaites & Freeston, 2005).…”
mentioning
confidence: 97%
“…A considerable portion of previous research on treatment acceptability and preference relies on student or nonclinical community samples (e.g., Bragesjö, Clinton, & Sandell, 2004;Ertl & McNamara, 2000;Heaven & Furnham, 1994;Mohlman, 2012;Tarrier, Liversidge, & Gregg, 2006). Of course, the ideal method for investigating treatment acceptability is to sample from treatment-seeking and/or clinical populations, although this approach would be time consuming and expensive.…”
mentioning
confidence: 99%